2017
DOI: 10.1099/jgv.0.000660
|View full text |Cite
|
Sign up to set email alerts
|

EBI2 expression in B lymphocytes is controlled by the Epstein–Barr virus transcription factor, BRRF1 (Na), during viral infection

Abstract: Epstein-Barr virus-induced gene 2 (EBI2) is an important chemotactic receptor that is involved in proper B-cell T-cell interactions. Epstein-Barr virus (EBV) has been shown to upregulate this gene upon infection of cell lines, but the timing and mechanism of this upregulation, as well as its importance to EBV infection, remain unknown. This work investigated EBV's manipulation of EBI2 expression of primary naive B cells. EBV infection induces EBI2 expression resulting in elevated levels of EBI2 after 24 h unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Furthermore, BRRF1 was reported to influence EBI2 expression in B lymphocytes directly 20 . In light of these studies, our results indicate that BRRF1 may affect host transcription, but its effect on EBV lytic replication may not be very strong.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BRRF1 was reported to influence EBI2 expression in B lymphocytes directly 20 . In light of these studies, our results indicate that BRRF1 may affect host transcription, but its effect on EBV lytic replication may not be very strong.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, low CCR7 and EBI2 expression levels are required to guide B cells into follicles where they differentiate into GC B cells ( 3 ). B cells in vitro infected with EBV show an EBI2 upregulation both in lytic and latent phases ( 62 , 63 ). Consequently, EBI2 high expression in EBV-infected B cells might favor a decreased GC formation.…”
Section: Modulation Of Humoral Immune Response By Viral Infection Of mentioning
confidence: 99%
“…Later, other groups have confirmed that EBI2 can be up‐regulated by EBV infection and EBV‐encoded proteins . The most detailed study of this to date is a recent study showing that the lytic EBV transcription factor BRRF1 is required for the EBV‐induced up‐regulation of EBI2 and that it is independently capable of increasing EBI2 expression in non‐infected B cells . However, the mechanism by which BRRF1 induces EBI2 expression is still unknown, and it is also not clear what the role of EBI2 may be during infection with EBV.…”
Section: Introductionmentioning
confidence: 99%
“…1 Later, other groups have confirmed that EBI2 can be up-regulated by EBV infection and EBV-encoded proteins. [2][3][4] The most detailed study of this to date is a recent study showing that the lytic EBV transcription factor BRRF1 is required for the EBV-induced up-regulation of EBI2 and that it is independently capable of increasing EBI2 expression in non-infected B cells. 4 However, the mechanism by which BRRF1 induces EBI2 expression is still unknown, and it is also Abbreviations: 7 ,25-OHC, 7 ,25-dihydroxycholesterol; CH25H, cholesterol 25-hydroxylase; CYP27A1, cytochrome p450 family 27 subfamily A member 1; CYP7B1, 25-hydroxycholesterol 7-alpha-hydroxylase; DC, dendritic cell; EAE, experimental autoimmune encephalitis; EBI2, EBV-induced gene 2; FDC, follicular dendritic cell; FRC, fibroblastic reticular cell; GC, germinal center; GPCR, G protein-coupled receptor; HSD3B7, 3 beta-hydroxysteroid dehydrogenase type 7; ICOS, inducible T cell co-stimulator; IDIN, IRF7-driven inflammatory network; IRF7, interferon regulatory factor 7; LPC, lysophosphatidylcholine; MS, multiple sclerosis; MZ, marginal zone; T1D, type 1 diabetes mellitus7; Tfh cell, T follicular helper cell; WT, wild-type not clear what the role of EBI2 may be during infection with EBV.…”
Section: Introductionmentioning
confidence: 99%